2014
DOI: 10.1364/boe.5.000485
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of two-dimensional light scattering patterns of cervical cell nuclei to map dysplastic changes at different epithelial depths

Abstract: Abstract:We use an extensive set of quantitative histopathology data to construct realistic three-dimensional models of normal and dysplastic cervical cell nuclei at different epithelial depths. We then employ the finitedifference time-domain method to numerically simulate the light scattering response of these representative models as a function of the polar and azimuthal scattering angles. The results indicate that intensity and shape metrics computed from two-dimensional scattering patterns can be used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…15,19,20 In the visible and near-infrared region, the absorption coefficient of the epithelial tissue is significantly lower than the scattering coefficient, and thus the measured attenuation coefficient approximates to the scattering coefficient. 27 The results revealed that the different layers of the epithelial tissue, such as the superficial, intermediate, and basal layers, show distinct morphologies and RI distributions. Although many methods have been demonstrated to measure the average RI of bulk tissue based on the focus-tracking or bifocal optical coherence tomography [23][24][25] and the critical angle method, 26 there is still no suitable method for obtaining the spatially resolved RI values of fresh epithelia.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…15,19,20 In the visible and near-infrared region, the absorption coefficient of the epithelial tissue is significantly lower than the scattering coefficient, and thus the measured attenuation coefficient approximates to the scattering coefficient. 27 The results revealed that the different layers of the epithelial tissue, such as the superficial, intermediate, and basal layers, show distinct morphologies and RI distributions. Although many methods have been demonstrated to measure the average RI of bulk tissue based on the focus-tracking or bifocal optical coherence tomography [23][24][25] and the critical angle method, 26 there is still no suitable method for obtaining the spatially resolved RI values of fresh epithelia.…”
Section: Introductionmentioning
confidence: 93%
“…21 These methods have limited accuracy because they rely on the assumptions of depth-independent reflectivity or backscattering cross section, 8,12,13,[15][16][17][18][19]22 a fixed fraction of the attenuated light being backscattered, 14 a certain spatial distribution of refractive indices (RI), 17 or a certain scattering phase function 12 in tissue. 27 As an alternative, Wang et al 28 and Xu 29 have proposed to determine the scattering coefficient from the spatial variance of the phase shifts and the physical thickness of thin slices of tissue blocks, based on the first-order Born approximation. Arifler et al obtained the RI distributions of stratified squamous epithelial tissue from Feulgen-thionin stained cervical biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the scattering coefficient is a promising biomarker for differentiating precancerous dysplasia from low-grade dysplasia or normal tissue [14][15][16][17]. However, the assumptions that the backscattering cross-section remains constant throughout the epithelial thickness may not be valid [18], rendering the estimation of scattering coefficients unreliable. Another group of techniques rely on detecting multiply scattered light which is also known as diffuse reflectance to estimate an average scattering coefficient of the tissue based on the radiative transport equation or Monte Carlo simulations for photon migration [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Su et al have recently developed the light scattering microfluidic cytometry for label-free single cell analysis by measurements of the two-dimensional (2D) light scattering patterns [20]. The 2D patterns are sensitive to the cellular microstructures and organelles such as nucleus and mitochondria [21][22][23].…”
Section: Introductionmentioning
confidence: 99%